2016
DOI: 10.1037/a0039151
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment against men: Examining the roles of feminist activism, sexuality, and organizational context.

Abstract: The current study investigated men's experiences of sexual harassment in the workplace, including sexually advancing harassment (e.g., unwanted touching) and gender harassment (e.g., derogatory comments). We examined the associations among engaging in feminist activism, being a sexual minority (e.g., gay, bisexual), and working in an organizational context that tolerates sexual harassment in predicting men's experiences of harassment. Moreover, we examined whether activism was protective against negative perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 84 publications
0
37
0
14
Order By: Relevance
“…Finally, we focused on male‐on‐female sexual objectification because women tend to report objectification and harassment to a greater degree than do men (e.g., Berdahl & Aquino, ; Gervais et al., ). However, it is possible that same‐gender sexual objectification such as men targeting other men, a common and increasingly frequent workplace complaint, is seen as sexually harassing, and that even women targeting other women, which is less common, could be a potential workplace problem (Holland, Rabelo, Gustafson, Seabrook, & Cortina, ). These are all important next steps for research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Finally, we focused on male‐on‐female sexual objectification because women tend to report objectification and harassment to a greater degree than do men (e.g., Berdahl & Aquino, ; Gervais et al., ). However, it is possible that same‐gender sexual objectification such as men targeting other men, a common and increasingly frequent workplace complaint, is seen as sexually harassing, and that even women targeting other women, which is less common, could be a potential workplace problem (Holland, Rabelo, Gustafson, Seabrook, & Cortina, ). These are all important next steps for research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…More recently, Holland et al. () found that men who engaged in feminist activism were more likely to become MM‐SBH targets. These examples, extant case law (e.g., Oncale v Sundowner Offshore Servs.…”
Section: Masculinity and Mm‐sbhmentioning
confidence: 99%
“…Berdahl () theorized that these same motivations drive SBH against men, but this has not been empirically demonstrated. Although harassment against men has received much less research attention (Berdahl & Raver, ), it nevertheless occurs, though less frequently than against women, and has deleterious consequences (Berdahl, Magley, & Waldo, ; Fitzgerald, Drasgow, & Magley, ; Holland, Rabelo, Gustafson, Seabrook, & Cortina, ; Konik & Cortina, ; Magley, Waldo, Drasgow, & Fitzgerald, ; Nielsen, Bjørkelo, Notelaers, & Einarsen, ; Stockdale, Visio, & Batra, ; Uggen & Blackstone, ; Waldo, Berdahl, & Fitzgerald, ). Understanding the impetus for this behavior is critical to addressing SBH against men, but despite academic (Berdahl et al., ; Nielsen et al., ) and public (Chandler, ; Scott, ; Yeginsu, ) accounts suggesting its incidence and severity, the psychological mechanisms motivating SBH toward men have not been systematically investigated.…”
mentioning
confidence: 99%
“…El término acoso sexual incluye lo que en Ciencias Sociales se denomina "acoso de género", es decir, aquellos comportamientos hostiles, insultos y/o actos degradantes que sirven para expresar actitudes insultantes u ofensivas hacia las mujeres (Expósito & Moya, 2005;Holland, Rabelo, Gustafson, Seabrook & Cortina, 2016). Además, el término también incluye la "atención sexual no deseada", haciendo referencia a aquellos actos sexuales ofensivos no deseados y no recíprocos, que abarca conductas verbales como expresiones, chistes y comentarios de doble sentido (Diehl, Rees & Bohner, 2016) y no verbales tales como la mirada objetivante (examinar las partes del cuerpo de otra persona), tocarse indebidamente o presionar a alguien para obtener citas (Expósito y Moya, 2005;Galdi et al, 2013).…”
Section: Introductionunclassified